(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
The prevalence of overweight among students of SMA Negeri 1 Samarinda is the main focus in efforts to improve adolescent health. The main objective of this activity is to increase students' knowledge regarding the risks and impacts of being overweight. So it is hoped that it can increase motivation for change at the student level. Education is carried out using an interactive lecture method through the poster media 'Recognize and Prevent Overweight'. Evaluation of effectiveness is carried out using the Wilcoxon test. The results of the study showed a significant difference between the level of student knowledge before and after counseling, with a significance value of 0.000 (p <0.05). This finding indicates that the use of posters as an educational medium is effective in increasing the knowledge of students of SMA Negeri 1 Samarinda. It is hoped that this research can increase adolescent awareness of the importance of a healthy lifestyle.